Discrimination in a low-wage labor market: a field experiment - Devah Pager; Bruce Western; Bart Bonikowski (Institute for the Study of Labor (IZA), 2009)
Decades of racial progress have led some researchers and policymakers to doubt that discrimination remains an important cause of economic inequality. To study contemporary discrimination we conducted a field experiment in the low-wage labor market of New York City. The experiment recruited white, black, and Latino job applicants, called testers, who were matched on demographic characteristics and interpersonal skills. The testers were given equivalent resumes and sent to apply in tandem for hundreds of entry-level jobs. Our results show that black applicants were half as likely to receive a callback or job offer relative to equally qualified whites. In fact, black and Latino applicants with clean backgrounds fared no better than a white applicant just released from prison. Additional qualitative evidence from our testers' experiences further illustrates the multiple points at which employment trajectories can be deflected by various forms of racial bias. Together these results point to the subtle but systematic forms of discrimination that continue to shape employment opportunities for low-wage workers.
Keywords: J7; 330; Discrimination; field experiment; race; labor markets; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Niedriglohn; Arbeitskräfte; Feldforschung; New York (NY)